ARCADO - Adding random case analysis to direct observation in workplace-based formative assessment of general practice registrars. Issue 1 (December 2015) - Ingham, Gerard; Fry, Jennifer; Morgan, Simon; Ward, Bernadette
Abstract Background Workplace-based formative assessments using consultation observation are currently conducted during the Australian general practice training program. Assessment reliability is improved by using multiple assessment methods. The aim of this study was to explore experiences of general practice medical educator assessors and registrars (trainees) when adding random case analysis to direct observation (ARCADO) during formative workplace-based assessments. Methods A sample of general practice medical educators and matched registrars were recruited. Following the ARCADO workplace assessment, semi-structured qualitative interviews were conducted. The data was analysed thematically. Results Ten registrars and eight medical educators participated. Four major themes emerged - formative versus summative assessment; strengths (acceptability, flexibility, time efficiency, complementarity and authenticity); weaknesses (reduced observation and integrity risks); and contextual factors (variation in assessment content, assessment timing, registrar-medical educator relationship, medical educator's approach and registrar ability). Conclusion ARCADO is a well-accepted workplace-based formative assessment perceived by registrars and assessors to be valid and flexible. The use of ARCADO enabled complementary insights that would not have been achieved with direct observation alone. Whilst there are some contextual factors to be considered in its implementation, ARCADO appears to have utility as formative assessment and, subject to further evaluation, high-stakes assessment.